A Case of Monozygotic Twins: The Value of Discordant Monozygotic Twins in Goldenhar Syndrome—OMIM%164210 - K. N. Venkateshwara Prasad; Arvind Rajha; Pradeep Kumar Vegi (Case Reports in Pediatrics, 2013)
Goldenhar syndrome is a rare developmental disorder characterised by hemifacial microsomia, epibulbar tumours, ear malformation, and vertebral anomalies. As monozygotic (MZ) twins are believed to be genetically identical, discordance for disease phenotype between MZ twins varies with craniofacial anomalies, cardiac, vertebral, and central nervous system defects sporadically. We report a case of monozygotic female twins discordant for Goldenhar syndrome with hemifacial microsomia and the dysplasia of auricular pinna.